2020
DOI: 10.3389/fcell.2020.559486
|View full text |Cite
|
Sign up to set email alerts
|

S100A10 Accelerates Aerobic Glycolysis and Malignant Growth by Activating mTOR-Signaling Pathway in Gastric Cancer

Abstract: S100 calcium-binding protein A10 (S100A10) is crucially involved in the tumorigenesis of multiple malignant tumors. Reprogrammed glucose metabolism is emerging as a hallmark of various human cancers. However, the function of S100A10 in aerobic glycolysis is unclear. The expression of S100A10 was analyzed using the Oncomine database, Gene Expression Profiling Interactive Analysis (GEPIA), The Cancer Genome Atlas (TCGA), and the UALCAN cancer database. Prognostic analysis was performed using the Kaplan–Meier Plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…Yan Li et al . found that S100A10 promoted glycolysis and proliferation by activing the mTOR pathway [ 29 ]. Besides, several inhibitors of the PI3K/Akt/mTOR signaling pathway were successfully developed in drug research and their efficacy was tested in gastric cancer with significant improvement [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yan Li et al . found that S100A10 promoted glycolysis and proliferation by activing the mTOR pathway [ 29 ]. Besides, several inhibitors of the PI3K/Akt/mTOR signaling pathway were successfully developed in drug research and their efficacy was tested in gastric cancer with significant improvement [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gastric cancer is a highly invasive and aggressive malignancy; therefore, the chance of survival depends on how early it is detected [ 184 , 220 , 221 , 222 ]. However, most gastric cancers are diagnosed in late stages when symptoms begin to appear.…”
Section: S100a10 As a Biomarkermentioning
confidence: 99%
“…More recently, Li et al [ 221 ] performed an extensive analysis of S100A10 levels in gastric cancer to investigate its potential mechanism in aerobic glycolysis often used by tumor cells. The databases used in this study were Oncomine, GEPIA, Kaplan–Meier Plotter, TCGA, GEO, GSEA, and UALCAN.…”
Section: S100a10 As a Biomarkermentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, these studies have indicated that p11 stimulates aerobic glycolysis in gastric cancer cells via activation of Src/ANXA2/AKT/mTOR signaling pathway, ultimately leading to enhanced cell proliferation and resistance to apoptosis. This is the first investigation directly implicating p11 in aerobic glycolysis [210]. Two recent studies have highlighted the importance of p11 in modulating gene expression of pluripotency factors in breast cancer stem cells (CSC).…”
Section: Involvement Of P11 In Biological Processes and Cancermentioning
confidence: 99%